Polityka spójności a wyzwania dla polityki rozwoju regionalnego w Polsce - Szostak, Ewa (The Cohesion Policy VS Challenges for Policy of Regional Development in Poland, 2006)
Cohesion, whose goal is decreasing development differences, has been a very important issue for the EU. The big differences in development between regions and increasing competitiveness are the results of globalization. Therefore the main issue of regional policy is building up the regions' competitiveness. The intensive interaction networks between producers, brokers and consumers are very important for development of regions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 341-347